Continuous Curvilinear Capsulorhexis in Cataract Surgery Using a Modified 3-Bend Cystotome - Yuan Zeng; Jian-hua Gao (Journal of Ophthalmology)
We modified a 2-bend cystotome for continuous curvilinear capsulorhexis (CCC) in manual or phacoemulsification cataract surgery to improve the safety and ease of performance. A 26G needle was converted into a cystotome with 3 bends. In this retrospective study, the performance of modified 3-bend cystotome was compared with conventional 2-bend cystotome. During cataract surgery, in the 3-bend cystotome group, mean completion time of CCC was shorter, mean times of viscoelastic agent supplement were less, and CCC success rate was higher than that in 2-bend group. Complication incidence, such as postoperative transient corneal edema and irreparable V-shaped tear, was also lower in 3-bend group. No posterior capsular rupture or no other complication was observed in either group. A polymethyl methacrylate intraocular lens or a hydrogel intraocular lens was implanted in the capsular bag in all eyes. We conclude that it is safe and efficient to accomplish a CCC using the 3-bend cystotome due to its ability to sustain the anterior chamber depth (ACD) and keep the posterior lip intact. Using the 3-bend cystotome also allowed for an adequate view into the anterior chamber from lack of wound deformation.